KINERJA PEGAWAI ADMINISTRASI KEUANGAN PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH PROPINSI SULAWESI TENGAH - Ariesta Parampasi, Dedi (Katalogis, 2015)
This Research Aimed At Finding Out The Work Performance Of Financial Administration Staff At The Assest And Financial Management Office Of Central Sulawesi Province. This Research Used A Qualitative Method By Employing Snowball Technique In Order To Select The Informants For The Research Purpose. The Techniques Used For Data Collection Were Observation, Interview, And Documentation. The Work Performance Of The Financial Administration Staff At The Asset And Financial Management Office Of Central Sulawesi Province Did Not Run Well. Of 7 Indicators Observed, 6 Ones Were Not Optimal. 1) Objective, In Terms Of Financial Administration Management, Did Not Go Through The Existing Mechanism. 2) Financial Administration Standart Was Not Implemented Well Due To The Absence Of Information System Of Provincial Financial Management Resulting In Frequently Late Report Submission.4) Tools Of Facilities Were Limited, Particulary Computer 5) Human Resource Competence Was Limited, Only 5 Staff And They Were In Contrast Wit Their Expertise. 6) Motivation Mechanism Was Not Optimal Due To The Absence Of Reward And Punishment Program For The Staff. The Research Indicates That Indicator. 3) Opportunity Has Run Well. All The Result Of The Financial Administration Process Areaccesable And Published.